Practice variation in the treatment of rheumatoid arthritis among German rheumatologists - Zink, A.; Listing, J.; Ziemer, S.; Zeidler, H.; German Collaborative Arthritis, Centres (J Rheumatol, 2001)
OBJECTIVE: To describe practice variation in the treatment of rheumatoid arthritis (RA) among German rheumatologists with regard to drug and non-drug therapy. METHODS: We used data of 7,326 patients with RA registered in a national German rheumatological database in 1998. In the database, every patient with an inflammatory rheumatic disease seen at one of the German Collaborative Arthritis Centres is registered once a year with a standard clinical data form and a patient questionnaire. We compared health care provided by 29 rheumatological outpatient units. For drug and non-drug treatment unit prescription rates, ranges and outliers were calculated. Logistic regression analysis was used for case mix adjustment and for the identification of practice patterns. RESULTS: We observed variation concerning the frequency of use of single disease modifying antirheumatic drugs (DMARD). The median of the prescription rates in the 29 units for methotrexate (MTX) was 55% in 1998 (1st quartile: 51%, 3rd quartile: 63%); sulfasalazine had a median of 15% (quartiles: 10%/19%), antimalarials a median of 8% (quartiles: 5%/21%). Combination DMARD therapy was used in 11% (quartiles: 6%/18%). Prescriptions of low dose steroids (< or = 7.5 mg) had a median of 45% (quartiles: 35%/55%), and nonsteroidal antiinflammatory drugs (NSAID) had a median prescription rate of 58% (quartiles: 50%/70%). High variation was also found concerning active physiotherapy (median: 41%; quartiles 34%/55%) and passive physical measures (median 14%, quartiles 9%/37%). Differences in case mix (age, sex, rheumatoid factor, disease duration, severity, disability) only explained a small proportion of the total variation. When the units were grouped according to the frequency of prescription of DMARD combination therapy, treatment patterns could be identified. Units with higher rates of DMARD combination therapy used more drugs for the prevention and treatment of osteoporosis, more active physiotherapy but fewer NSAID and fewer passive physical therapies. CONCLUSION: Variation in drug and non-drug treatment indicates significant differences in health care provision. Trends in the drug management of RA are adopted differentially by the members of the rheumatology community. The large variability in non-drug therapies may, apart from differences in availability, suggest a lack of agreement on therapeutic effectiveness.